Study on Sintered Wick Heat Pipe (SWHP) with CuO Nanofluids under Different Orientation. (25th August 2022) - Kumar, P. Manoj; Saminathan, Rajasekaran; Tharwan, Mohammed; Hadidi, Haitham; Stalin, P. Michael Joseph; Kumaresan, G.; Ram, S.; Rinawa, Moti Lal; Saravanakumar, P. T.; Karthikeyan, K.; Gebreyohannes, Dawit Tafesse
Abstract : The current work investigates the performance of cylindrical-shaped sintered wick heat pipe at different orientations, numerically. The results are compared and validated with the experimental findings. The study is extended by using a nanofluid (comprising nano-Curo in deionized water) as a working fluid and the thermal performance of heat pipe with deionized (DI) water has been compared with that of heat pipe with nanofluid (containing various concentrations of CuO nanoparticles in DI water). During the investigation, the nanofluid with 1.0 weight fraction of CuO nanopaticles found to be optimum, which has produced the better results. The numerical analysis has been carried out to study the temperature difference, fluid velocity, and pressure drop of the sintered wick heat pipe using the commercial CFD software, Ansys Fluent R14.5. The computational results are observed to be much closer to the experimental data, and the vapor velocity at the heat pipe's core has been determined to be 64.54% higher than the liquid flow over the wick structure. Interestingly, the heat pipe pressure drop has been reduced by adding CuO nanoparticles to the working fluid. Finally, the heat pipe loaded with a 1.0% concentration of nano-CuO in nanofluid has exhibited a notable reduction in pressure drop of 35.33%.